The effect of varied dietary crude protein levels with balanced amino acids on performance and egg quality characteristics of layers at first laying phase (2012)
"Four diets were formulated to study the influence of varying crude protein levels on the performance, egg quality, serum and haematological characteristics at the first phase of laying cycle of sixty Bovan Nera laying birds that were randomly allotted to dietary treatments. The four experimental diets had five replicates each and three birds per replicate. Diet 1 contained 14% crude protein (CP), while diet 2 contained 15% CP, diets 3 and 4 contained 16% and 17% CP respectively. The experimental birds were fed for 10 weeks and the data collected were statistically analysed. Apparent variations recorded for all the performance characteristics such as Egg number, Hen-day production, Feed Conversion Ratio (FCR) and weight gain were significantly different (p < 0.05). The best FCR value were recorded by birds fed 17% CP (3.45), while the highest weight gain mean value were also recorded by birds fed 17% CP value. Findings indicated a direct relationship between dietary crude protein values and performance. "